The association between febrile convulsion in children and chronic hyperventilation in parents - M. Widiastuti Samekto; I Gusti Putu Ardana (Paediatrica Indonesiana, 2002)
Background Febrile convulsion and chronic hyperventilation syndrome (spasmophilia) are suspected to share the same root of pathophysiology, a genetic trait abnormality related to ion channel that could cause neuronal hyperexcitability.Objective To determine the prevalence ratio of parents with chronic hyperventilation syndrome between two groups of children with and without febrile convulsion.Methods A cross-sectional design study was used, with a tertiary hospital setting (Kariadi Hospital). Participants were selected consecutively based on eligibility criteria. Febrile convulsion was diagnosed based on a modified Livingstone criteria. Chronic hyperventilation syndrome in parents was determined using the clinical diagnostic test of spasmophilia (88.4% sensitivity and 6 1.6% specificity). Statistical calculations were conducted with two by two table analysis and within the 95% confidence interval.Results Sixty-two children (mean age 18 months) who met the eligibility criteria were included. The parents' mean ages were 33 years (father) and 29 years (mother). The prevalence ratio of father, mother and both parents with chronic hyperventilation between the febrile convulsion group and the non-febrile convulsion group were 2.56 (95% CI 0.53 to 12.31), 6.19 (95% CI 1.70 to 22.6) and 18.7 (95% CI3.07 to 113.9), respectively.Conclusion Febrile convulsion can be anticipated in children of parents who suffer from chronic hyperventilation syndrome.